New species of tree cricket Oecanthus Serville, 1831 (Orthoptera: Gryllidae: Oecanthinae) from Reserva Natural Vale, Espírito Santo, Brazil, with chromosome complement - Milach, Elisa Machado; Costa, Maria Kátia Matiotti Da; Martins, Luciano De Pinho; Nunes, Lorena Andrade; Silva, Daniela Santos Martins; Garcia, Flávio Roberto Mello; Oliveira, Elliott Centeno De; Zefa, Edison (Zootaxa, 2016)
A new species of the genus Oecanthus Serville, 1831 from Reserva Natural Vale, state of Espírito Santo, Brazil is described. The new species differs from other of this genus in characteristics of the pseudepiphallus main lobe, endophallic sclerites, posterior median lobe of the metanotal gland and black spots on the femora and tibiae. The chromosome number is 2n=16+XY♂=18 and 2n=16+XX♀=18, and this complement present one pair of autosomes less than the other five cytological studied species.